Commentarii de tumultu Gedanensi ([Mikołaj Scharffenberger], 1577)
Wojna Stefana Batorego z Gdańskiem (1576-1577)
Data wydania: M.D.LXXVII
Keywords: Publicystyka; Polska; Wojna; Gdańsk (woj. pomorskie)